Improved Antitumor Outcomes for Colon Cancer Using Nanomicelles Loaded with the Novel Antitumor Agent LA67 - Cui M (Dove Medical Press, 2020)
Minhu Cui,1,2 Mingji Jin,2 Mingfeng Han,2 Yingda Zang,2 Chuangjun Li,2 Dongming Zhang,2 Wei Huang,2 Zhonggao Gao,2 Xuezhe Yin3 1Department of Gastroenterology, Yanbian University Hospital, Yanji 133000, Jilin, People’s Republic of China; 2State Key Laboratory of Bioactive Substance and Function of Natural Medicines, Institute of Materia Medica, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing 100050, People’s Republic of China; 3Department of Respiratory Medicine, Yanbian University Hospital, Yanji 133000, Jilin, People’s Republic of ChinaCorrespondence: Zhonggao GaoState Key Laboratory of Bioactive Substance and Function of Natural Medicines, Institute of Materia Medica, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing 100050, People’s Republic of ChinaTel/Fax +86 10-63028096Email zggao@imm.ac.cnXuezhe YinDepartment of Respiratory Medicine, Yanbian University Hospital, Yanji 133000, Jilin, People’s Republic of ChinaTel/Fax +86-433-2817019Email yinxz1234@163.comBackground: LA67 is a derivative of triptolide that exhibits strong antitumor activity. This derivative has a better safety profile than triptolide, but is limited by poor aqueous solubility.Aim and Methods: To improve solubility and further increase therapeutic efficacy, we prepared LA67-loaded polymeric micelles (LA67-PMs) using a film hydration method. The physicochemical properties of LA67-PMs were investigated, and the antitumor activity of this formulation against Colon26 (C26) cancer cell line was evaluated in vitro and in vivo with LA67 as a control.Results: Polymeric micelles containing LA67 had a particle size of 17.88 nm and a drug entrapment efficiency of 94.84%. This formulation dispersed completely in aqueous solution and exhibited slow, sustained release of LA67. Cellular uptake assay showed that LA67-PMs delivered LA67 to cancer cells with greater efficiency than free LA67, which resulted in increased LA67 accumulation in cancer cells. Cell counting kit 8 (CCK-8) assay showed that blank polymeric micelles (PMs) exhibited low toxicity and LA67-PMs exerted pronounced anti-proliferation effects against C26 cells. Furthermore, LA67-PMs induced apoptosis and repressed migration more effectively than free LA67. In vivo evaluation of antitumor activity showed that LA67-PMs inhibited tumor growth and distant organ metastasis to a greater extent than LA67, which resulted in improved survival rate. The potential mechanisms of these effects may have been induction of apoptosis, inhibition of cell proliferation, and neovascularization.Conclusion: Our study showed that LA67-PMs may be a promising formulation for treatment of colon cancer.Keywords: triptolide derivatives, polymeric micelles, small size, tumor therapy